A Mathematical Framework for Interpreting Playing Environments as Media for Information Flow. (28th August 2008) - Motoyoshi, Tatsuo; Hattori, Takashi; Kawakami, Hiroshi; Shiose, Takayuki; Katai, Osamu
Abstract : This paper proposes a novel strategy of designing play equipments. The strategy introduces two loose constraints as a guideline for designers. The first constraint is "describing unit of play action chain_〈 O, S, V 〉 based on Barthes_ semiology, and the second is the infomorphism between designer, play equipment, and players based on channel theory. We provide detailed explanation of the strategy through an example of a designing process of playing environment where the players usage of the play equipment cannot be foreseen.